The Effect of Tax Planning on Earnings Management - Tony R Sinambela; Tongam Sinambela (ProBisnis : Jurnal Manajemen, 2022)
This study aims to determine the effect of tax planning on earnings management. In this study the data used came from audited annual financial reports obtained from the website www.idx.co.id. This type of research is quantitative research. Determination of the sample was carried out using a purposive sampling technique, so that a sample of 16 companies was found. The analysis tool uses simple linear regression with panel data models. Based on the results of the t test research that tax planning has a significant effect on earnings management with a significant value of 0.0240 <0.05.